Študijsko gradivo pri predmetu Obligacijsko pravo - III: Institucije obligacijskega prava, integrirani študijski pripomoček z nalogami in usmeritvami - Samec Berghaus, Nataša; Bitrakov, Andrej; Drnovšek, Klemen (University of Maribor Press, 2025)
Study Material for the Course Law of Obligations - III: Institutions of the Law of Obligations, Integrated Study Tool with Tasks and Guidelines. The study material is designed as an integrated tool for undergraduate law students at the Faculty of Law, University of Maribor, attending the course Law of Obligations. The material supports flipped and problem-based learning methods, incorporating theoretical questions, statements, and practical examples that deepen students’ understanding of the subject matter. Each chapter provides study guidelines, an overview of key concepts, and exercises to reinforce knowledge. The material helps students develop analytical skills and legal reasoning, which are essential for successfully solving legal problems both during their studies and in their future careers. In addition to preparing students for the Law of Obligations exam, this material is also useful for deepening knowledge in other subjects related to civil and commercial law.